Anti-NMDA receptor encephalitis with initial negative markers: diagnostic and therapeutic challenges of a refractory case with 9-month-long follow-up. Issue 6 (28th June 2022) - Cascardo, Camilla; Ismail, Alexander; Fullmer, Joseph; Davila, Francisco
Abstract : Anti- N -methyl-d-aspartate (NMDA) receptor encephalitis is a progressively debilitating, frequently fatal disease caused by autoantibodies against the NMDA receptor. Risk of delayed treatment is high due to variable presentations, lack of awareness and potential false negative diagnostic studies. In this case report, a woman in her 20s presented with psychiatric manifestations and rapidly declined. Dyskinetic movements and dysautonomia were observed. Initial cerebrospinal fluid and serum anti-NMDA receptor antibodies were negative. MRI was inconclusive. Electroencephalography demonstrated extreme delta brush. Pelvic CT revealed an adnexal teratoma. She remained refractory to treatment until day 126 when, after two cycles of cyclophosphamide, she started to improve. She participated in rehabilitation with eventual discharge home on day 269. Recognising the variable presentations of anti-NMDA receptor encephalitis is important in avoiding misdiagnosis and delayed treatment. If clinical suspicion remains high despite negative results, repeat testing should be pursued. Clinical response should guide treatment decisions in refractory cases.